ANALISIS TEMPERATUR DAN UAP AIR BERBASIS SATELIT TERRA/AQUA (MODIS, LEVEL-2) (ANALYSIS OF TEMPERATURE AND WATER VAPOR BASED ON THE TERRA/AQUA SATELLITE (MODIS, LEVEL-2)) - Sinta Berliana Sipayung; Krismianto Krismianto; Risyanto Risyanto (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2016)
Terra and Aqua satellites that consist of multiple sensors including MODIS instruments, which is operated to detect the phenomena that exist on land, sea and atmosphere. Not a lot of data extracted especially for Indonesia region the associated with atmospheric data, because the product is still in the raw data (level-0). For data extraction of level-0 to level-2 needed software IMAPP (International MODIS/airs Processing Package) so displays some data atmospheric parameters including MOD 04 - Aerosol, MOD 05 - Total precipitable Water (Water Vapor), MOD 06 - Cloud, MOD 07 - Atmospheric Profiles, MOD 08 - gridded Atmospheric and MOD 35 in HDF4 format (Hierarchical Data Format-4) swath. This paper discussed only MOD07/MYD07 atmospheric profiles level-2 related parameters such as the temperature of the atmosphere at an altitude of 780 hPa and water vapor at a height of 700 hPa. This study aimed to analyze the phenomena in the atmosphere, based on extraction method Atmospheric Profiles in the resolution 1km, that consists of temperature and moisture level2, in the format hdf4 daily swath into data daily and monthly grid in .dat format, in the period of December 2014, January, July, and August 2015, especially in the area of Indonesia. The comparison between the results of the extraction swath and grid data from Terra/Aqua MODIS, that parameter atmospheric for the temperature has R-sqare an average of 0.72 and water vapor 0.74, while the RMSE temperature and water vapor are 0.88 and 0.29. ABSTRAK Satelit Terra dan Aqua yang terdiri dari beberapa sensor diantaranya instrumen MODIS, yang dioperasikan untuk mendeteksi fenomena yang ada di darat, laut, dan atmosfer. Belum banyak data yang diekstrak khususnya untuk wilayah Indonesia yang terkait dengan data atmosfer, karena produk MODIS masih berupa data mentah (level-0). Untuk ekstraksi data dari level-0 menjadi level-2 dibutuhkan software International MODIS/AIRS Processing Package (IMAPP) sehingga menampilkan beberapa data parameter atmosfer diantaranya MOD 04 - Aerosol, MOD 05 - Total Precipitable Water (Water Vapor), MOD 06 - Cloud, MOD 07 - Atmospheric Profiles, MOD 08 - Gridded Atmospheric dan MOD 35 swath dalam format Hierarchical Data Format-4 (HDF4). Pada makalah ini yang dibahas hanya MOD07/MYD07 atmospheric profiles level-2 yang berkaitan dengan parameter atmosfer seperti temperatur pada ketinggian 780 hPa dan uap air pada ketinggian 700 hPa. Penelitian ini bertujuan untuk menganalisis hasil ekstraksi data Atmospheric Profiles dari format HDF4 swath harian menjadi data grided harian, bulanan dalam format .dat serta aplikasinya pada periode bulan Desember 2014, Januari, Juli, dan Agustus 2015, khususnya wilayah Indonesia dalam resolusi 1km yang terdiri dari temperatur dan uap air level-2. Perbandingan antara hasil ekstraksi data MODIS swath dan data MODIS grided Terra/Aqua untuk parameter temperatur atmosfer mempunyai R-sqare rata-rata 0.72 dan uap air 0.74, sedangkan RMSE untuk temperatur dan uap air sebesar 0.88 dan 0.29.